Brief cycles of lower-limb occlusion accelerate recovery kinetics in soccer players - Daab, W.; Bouzid, M. A.; Lajri, M.; Bouchiba, M.; Rebai, H. (The Physician and Sportsmedicine, 2021)
Objective: The aim of this study was to assess the effect of intermittent vascular occlusion (IVO) on recovery following simulated soccer physical demand test in soccer players.